2018
DOI: 10.1051/e3sconf/20183201018
|View full text |Cite
|
Sign up to set email alerts
|

CFD simulation of a cabin thermal environment with and without human body – thermal comfort evaluation

Abstract: Nowadays, thermal comfort became one of the criteria in choosing a vehicle. In last decades time spent by people in vehicles had risen substantially. During each trip, thermal comfort must to be ensured for a good psychological and physical state of the passengers. Also, a comfortable environment leads to a higher power concentration of the driver thereby to a safe trip for vehicle occupants and for all traffic participants. The present study numerically investigated the effect of human body sited in the drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…4). The dimensions of the human body model were chosen to fit the scale of our human body numerical models and keeping the proportions of one thermal manikin that was developed in our team [7] [8].…”
Section: Experimental Model Designmentioning
confidence: 99%
“…4). The dimensions of the human body model were chosen to fit the scale of our human body numerical models and keeping the proportions of one thermal manikin that was developed in our team [7] [8].…”
Section: Experimental Model Designmentioning
confidence: 99%
“…The development of microclimate regulation systems is presented in papers [8,21,27,28], and the assessment of their performance by such indicators as energy consumption, thermal comfort and air quality is presented in papers [6,12,13,29,30,31,32,33]. Theoretical studies of microclimate regulation systems and microclimate effect on humans are based on computer models described in papers [3,5,7,9,10,25,27,28,29,33]. The papers [35,36] provide a comparative analysis and assessment of the possibilities of various implementations of mathematical models of gas thermodynamics on computers.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of arising subjective sensations of passengers under certain microclimatic conditions is presented in papers [7,17,26]. Different schemes of microclimate regulation and thermal comfort provision for different types of wheeled vehicles have been studied in papers [9,20,29]. Assessment of changes in microclimate parameters in time and various driving conditions of a wheeled vehicle has been performed in papers [11,15,16,19].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature review, it was found out that researchers focused their attention on motorization and HVAC systems mainly for automobile cabins, for example [2], [3], [4], [5], [6], [7]. For the railway industry, CFD simulation tend to focus on airflow simulations in carriages, for example [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, drivers can become fatigued easily. A comfortable vehicular climate not only helps to reduce the driver stress but also guarantees good visibility by avoiding the fog phenomenon, and thus contributing to safer driving [5]. It is also important due to the fact that rail freight transport is widely used and prevalent in many countries around the world.…”
Section: Introductionmentioning
confidence: 99%